Joint suppression method for range-Doppler ambiguity sidelobes in DTMB-based passive bistatic radar - Yong Wu; Luo Zuo; Jue Wang; Dan Wang (Scientific Reports)
Abstract To mitigate the impact of the suboptimal ambiguity function of digital television terrestrial multimedia broadcasting (DTMB) signal, used as the illuminator of opportunity in passive bistatic radar, this paper provides a detailed analysis of the ambiguity function characteristics based on the physical structure of the DTMB signal frame. It elucidates the mechanisms behind intra-frame and inter-frame range sidelobes, as well as Doppler sidelobes. Building on this analysis, a novel joint method for suppressing range-Doppler ambiguity sidelobes is proposed to achieve unambiguous target detection. The proposed method effectively removes various types of ambiguity peaks while minimizing mainlobe loss. Simulations and experimental data validate the accuracy of the analysis and demonstrate the effectiveness of the proposed method.